Social enterprise in Europe: recent trends and developments - Defourny, Jacques; Nyssens, Marthe (Social enterprise journal, 2008)
Purpose - Twelve years ago, the concept of social enterprise was rarely discussed in Europe, however it is now making significant breakthroughs in European Union (EU) countries. Within this context, the purpose of this paper is to synthesize major evolutions experienced by social enterprises across Europe and the key challenges they are facing; and specific members of the EMES European Research Network provide a more in-depth update as to current trends and debates in their respective countriesDesign methodology approach - This paper is based on a comparative analysis of the different institutions (legal frameworks, public policies, supporting structures, public procurement policies ...) which support the development of social enterprises in the different EU countries. To delimit the field, the paper relies on the "ideal-type" social enterprise as defined by the EMES network: "Social enterprises are not-for-profit private organizations providing goods or services directly related to their explicit aim to benefit the community. They rely on a collective dynamics involving various types of stakeholders in their governing bodies, they place a high value on their autonomy and they bear economic risks linked to their activity".Findings - It was found that although the concept of social enterprise itself has not gained the same recognition in all EU countries (and is even still poorly understood in several of them), the reality is that growth and social enterprise are being experienced in most EU countries.Originality value - If the concept of social enterprise is on the public agenda of several EU countries, the understanding as well as the institutions to support their development vary from one country to the other. This paper provides a comparative analysis of this heterogeneous but rich landscape.